The Students’ Reflection on Hybrid Learning Environment at Higher Education Level post-COVID-19 Pandemic: Opportunities, Barriers, and Deal with Hybrid Learning - Haryati, Haryati; Suhayati, Lisa; Sitepu, Setiana Sri Wahyuni (FKIP Universitas Lampung, 2024)
The Students’ Reflection on Hybrid Learning Environment at Higher Education Level post-COVID-19 Pandemic: Opportunities, Barriers, and Deal with Hybrid Learning. The implementation of remote learning and face-to-face leaning environment can be assumed as hybrid learning. It obtains its popularity since students and lectures are in the period of Covid-19 pandemic to endemic period. To systematize the hybrid learning, lectures need to be familiar with the kind of technology to create interactive learning activities in online learning and have physical activities in the conventional way or classroom activities. It also offers distinctive learning practices; students achieve technological and practical knowledge. Objectives: The study aims to explore the students’ reflection on hybrid leaning. The reflection covers the opportunities they obtain, barriers they face and how they deal with hybrid learning. Methods: The students’ reflection will be obtained through the questionnaire and observation during the onsite and remote learning activities. The observation will be conducted within 6 months in order to have eligible data. Findings: The writers hope that the further findings will portray the students’ reflection in implementation of hybrid classes. Moreover, it is expected to enlighten the effectiveness and simplicity of remote learning and onsite learning environments. Conclusion: The most significant effect is the success of teaching and learning goals, and it will be the endless program in educational areas. Hence, lecturers and students are able to achieve the success of learning processes. Keywords: face-to-face, hybrid, learning, online.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024114